Pelaksanaan Pembinaan Bahasa dan Sastra Indonesia di SMP berdasarkan PP No. 57 Tahun 2014 Bab V - Inne Pelangi; Dita Mulyana Ramadhani; Nurul Maghfirah; Rahmah Rahmah (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to examine the development of language and literature in the learning process. This research includes descriptive qualitative research using sociolinguistic approach. Sources of data in this study is a junior high school class IX. Research data in the form of student speech in the learning process. Data collection is done through observation technique and record. Data analysis is done through three stages of the flow model, ie data reduction, data presentation, and data verification. The results showed that it can be concluded that (1) condition of Indonesian language development in learning process in SMP Negeri 1 Bontomarannu still less attention. This condition is seen from the tendency of students to mix the use of Indonesian language with the mother tongue (Makassar language) when the learning process takes place; (2) Factors contributing to the low level of Indonesian language development in the learning process at SMP Negeri 1 Bontomarannu, namely the lack of containers to develop the language and literature, the lack of awareness of language development in schools, and the strong influence of the use of regional languages; (3) Based on the factors causing the low level of Indonesian language development then the efforts that can be taken to improve the Indonesian language development in the learning process in SMP Negeri 1 Bontomarannu is to provide a container to nurture the creativity of students, restrict the use of English, local languages, and slang language in formal communications, and conduct language extension activities outside the language and literature months.